The effect of Valsalva maneuver on diastolic filling indices in patients with essential hypertension. - Mahdi, Salam A.; Mohammed, Najeeb H.; AL-Saffar, Hilal B. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Left ventricular hypertrophy and diastolic dysfunction are considered to be an important risk factor for cardiovascular morbidity and mortality in asymptomatic hypertensive patients. At the bedside, left ventricular geometric remodeling and diastolic dysfunction in hypertension can not be diagnosed without echocardiography which is a useful adjunct to the medical history, physical examination, ECG, and chest radiography. Hence, it provides an opportunity for good management and prognosis of what appears to be preclinical hypertensive complication. Subjects and Methods: 127 subjects with essential hypertension of either sex attending echo unit were subjected to medical history, clinical examination, physical measurements, ECG, M-mode and Doppler echocardiography. They were classified as 46 treated hypertensives where they were on regular antihypertensive medication, and 81 untreated hypertensive patients. In addition, they were sex and age matched to 39 healthy subjects who served as control group. Results: The results of this study revealed that hypertensive patients especially those with stage II hypertension were prone to develop left ventricular hypertrophy (LVH) of concentric geometric pattern and diastolic dysfunction. However, small percentage of those patients found to have diastolic dysfunction despite they were without LVH. In addition, Doppler echocardiography clarify that hypertensives with abnormal transmitral inflow profile; of left ventricular impaired relaxation pattern suffered left ventricular systolic dysfunction. Moreover, in this study there was no evidence of pseudonormal transmitral inflow filling pattern which is excluded after Valsalva maneuver. Conclusion: There is a strong association between left ventricular hypertrophy and diastolic dysfunction which was more common in patients with stage II hypertension. However, left ventricular diastolic dysfunction is usually follows left ventricular hypertrophy, but it still may proceed especially in those patients with left ventricular hypertrophy (LVH) of concentric geometric pattern. In addition, left ventricle diastolic dysfunction is not necessary coincide with the development of systolic dysfunction, namely normal ejection fraction and fractional shortening.